(untitled) (International Journal of Engineering and Computer Science, 2017)
Data is vulnerable at many points in any computer system, and many security techniques and types of functionality can be applied to protect it. Sulimanyah Court is a big and popular Government sector in Iraq. Many clients accessing E-Court Systems, SES (Sulimanyah E-Court Systems) is using SQL SERVER database to store and accesses court cases with different clients. Most of the security models available for databases today protect them from outside, unauthorized users and cannot be provides internal security in relationship with the user type of access to the database. This database can access by hundreds of clients. We propose a framework to increase security needs of database systems. Clients in this approach can be analysed to instituting sub channels between specific (groups of) users such that authorized subchannels appropriating from accessing objects that contain some sensitive information and restricting unauthorized users. In this paper we propose a general framework for Multi-Level Security (MLS) in Sulaymaniyah E-Court database.